Removal mercury from wastewater by electrocoagulation using iron plate as electrode - Mohd Amirul Hakim, Hamidi (2013)
Electrocoagulation is the removal process that based on electricity which used electrolysis concept. This process can remove contaminant like mercury which cannot be removed through filtration. This technique is economic and environmental friendly for wastewater treatment. Research studied was performed using synthetic mercury to determine the efficiency of mercury removal using this process. The objective of this research is to investigate the efficiency of mercury removal using iron electrode using different parameters including flow rate, charge loading and distance between electrodes. Electrocoagulation OT-1 model was used to perform the experiment and conductivity meter was used to perform the analysis. After all the analysis were performed its shows significant result which is about 90.10% of mercury successfully removed from the synthetic mercury solution. The highest flow rate 160 L/h and longest distance between electrodes 5cm contributed to the result of 90.10% removal of mercury from synthetic mercury solution. The highest charge loading also play importance role on removal of mercury.